First Language Phonological Acquisition by a Two Years Old Mandailing Child - Wildan Iskandar; Lince Sihombing; D.P. Tampubolon (Universitas Negeri Medan, 2015)
This study focused on describing: (1) what phones are acquired by a two years old Mandailing child. (2) how a two years old Mandailing child acquires the phonology production. (3) how the phonological productions of the words acquired by a two years old Mandailing child. A qualitative research was applied. The findings indicated that kinds of word are noun, adjective, verb and adverb and the most aspect of phonology found in this study is noun. The subject acquired the words through interaction with his family and sometimes used body language when he talked with his parents. The phonological production of the words acquired by the subject with several processes out of the twelve processes. Based on the findings, there are some suggestions: (1) Parents have to guide his child in learning to communicate as good as possible in order to the child can communicate well and effectively with other people in his environment, (2) In order to make a good communication and conversation, it is suggested to make approach to the child’s behaviors and habitual, (3) If parents want their child can acquire words well, they have to introduce words well and also guide him to pronounce it every day when they talk with him. Keywords: Child; Language Acquisition; and Phonology